Zdrowie dziecka po rozwodzie i wspólna opieka nad dziećmi = Child health after divorce and Joint Child Custody - Dončevová, Silvia (Vilnius: Mykolas Romeris Universitetas)
The study analyzes the impact of the divorce situation on the child's mental and physical health and the possibilities of helping and promoting social pedagogy in eliminating the negative effects of divorce on the health of the child. After divorce, a situation often occurs when parents think only about their needs rather than the needs of their children - in the social pedagogical practice we see the fatal consequences of this parental action on the child's health (in the best case, these children end up in the hands of social educators and other professionals in schools, school clubs or counseling centers).
Keywords: zdrowie dzieci; rozwód; opieka zastępcza; pedagogika społeczna; child`s health; divorce; alternative child custody; social pedagogy